Relativistic Binary Precession: Impact on Eccentric Massive Binary Black Hole Accretion and Hydrodynamics - Stanislav DeLaurentiis; Zoltán Haiman; John Ryan Westernacher-Schneider; Luke Major Krauth; Jordy Davelaar; Jonathan Zrake; Andrew MacFadyen (The Astrophysical Journal)
Recent hydrodynamical simulations have shown that circumbinary gas disks drive the orbits of massive binary black holes (BHs) to become eccentric, even when general relativistic (GR) corrections to the orbit are significant. Here, we study the GR apsidal precession of eccentric equal-mass massive binary BHs in circumbinary disks via two-dimensional hydrodynamical simulations. We perform a suite of simulations comparing precessing and nonprecessing binaries across a range of eccentricities, semimajor axes, and precession rates. We find that the GR precession of the binary's semimajor axis can introduce a dominant modulation in the binary's accretion rate and the corresponding high-energy electromagnetic light curves. We discuss the conditions under which this occurs and its detailed characteristics and mechanism. Finally, we discuss the potential to observe these precession signatures in electromagnetic- and gravitational-wave observations, as well as the precession signal's unique importance as a potential tool to constrain the mass, eccentricity, and semimajor axis of binary merger events.